Hepatitis E viral infection in pregnant ladies, a challenge for obstetricians and physicians - Jamil, Samia; Muhammad Sajid Jehangir, Hafiz; Naeem, Hamza; Maqsud, Mahliqa; Ayyaz, Mehwish; Kanwal, Tayyaba; Zahoor, Sarmad; Umer Mukhtar, Muhammad; Muhammad Atif, Malik; Manzoor Haideri, Raza (International Journal of Medicine, 2021)
Background: Hepatitis E Virus (HEV) is the major cause of morbidity and mortality in pregnancy. The virus was detected about three decades ago. The incidence and severity during pregnancy vary widely around the world.Material & Methods: This observational retrospective study was conducted from March 2019 to February 2020 in Obstetrics & Gynecology Department of Lady Aitchison Hospital, Lahore. 70 pregnant women with hepatitis E were subjected to detailed history taking. The diagnosis was based on positive Hepatitis E IgM (Anti HEV IgM) antibody on laboratory test in current pregnancy in antenatal period up to 42 days post partum were included.Results: Out of 70 pregnant women with Hep E IgM+ve, 3 (4.3%) women had Obstetrical hysterectomy as complications, with mean age of 26.0 ± 4.69 years. The mean gestational age when infection occurred was 31.12 ± 5.18 weeks. Among all females 9 (13%) patients expired due to fulminant hepatic failure, 12 (17.14%) females gave birth via spontaneous vaginal delivery (SVD),17(24.2%) females gave birth via C-Section. 30 (42.8%) females were manage conservatively.Conclusion: Hepatitis E viral infection in pregnant females is a life threatening condition. The study showed that pregnant women with jaundice and hepatitis E virus infection had a high mortality rate during third trimester. Early diagnosis and management will help in the control of the disease and prevents its complications.